The Effectiveness of Conditional Cash Transfer Program: A Case of Rural and Urban Beneficiaries in Philippines - Capulong, Charlyn Maybituin; Cuevas, Agham C (Journal of Economics Research and Social Sciences, 2024)
This paper analyzes the effectiveness of the Conditional Cash Transfer (CCT) program in the Philippines in terms of its effect on conditionality goods as reflected by food, health, and education expenditures of households from rural and urban areas that benefitted the program. The CCT program in the Philippines is known as Pantawid Pamilyang Pilipino Program (4Ps) that seeks to address the problem on poverty by improving the socioeconomic status of poor households through targeted investments in health and education. This study used the Propensity Score Matching methodology in estimating the average treatment effect on the treated to capture the effect of CCT on conditionality goods. The study finds that CCT has a significant effect on education for household beneficiaries in rural areas and has improved the quality of food consumed by household beneficiaries in urban areas. Also, a decreased in the per capita total expenditure and per capita food expenditure of the household beneficiaries is revealed in urban areas driven by their improved saving behavior. Thus, the CCT program, at some point, is effective in meeting its short-term goal, but it must be more targeted in order to improve its impact on other conditionality goods.